Development of Epoxy-Polyester Composite with Improved Thermophysical Properties for Restoration of Details of Sea and River Transport - A. Buketov; M. Brailo; S. Yakushchenko; A. Sapronova (Advances in Materials Science and Engineering)
The results of the experimental investigations of the optimization of the content of the polyester resin in the epoxy binder are shown in the work. It was determined that composite with concentration of the polyester (q = 10 mas.fr.) was characterized by the maximal values of the thermophysical properties. The Martens thermal resistance temperature, the linear shrinkage, the thermal coefficient of linear expansion, and the glass transition temperature of the epoxy-polyester matrix were investigated. It was found that introducing the polyester resin into the epoxy oligomer in quantity of q = 10 mas.fr. leads to improving the Martens thermal resistance of the material to the T = 352 K and decreasing the linear shrinkage to the Δl = 0.06%. The nonlinear dependence of the TCLE on the temperature was confirmed, and the tendency of changes in their values, depending on the content of polyester resin, was defined. The dilatometric curves were analyzed, and the glass transition temperature of developed epoxy-polyester matrix was determined at the level Tс = 318 K.